THE CHARACTER OF PENCAK SILAT ATHLETES IN CENTRAL JAVA 2023 - Muhammad Amin Rois; Sapta Kunta Purnama; Febriani Fajar Ekawati (2024)
The purpose of this study was to to describe the character values ​​of 5T (Taqwa, Tanggap, Tangguh, Tanggon, and Trengginas) in Pencak Silat athletes. This research is qualitative research using a case study research design. This research was conducted at the Pusat Pendidikan dan Latihan Olahraga Pelajar (PPLOP) of Central Java. This study is qualitative research using a case study research design. The primary data source in this research was eight Pencak Silat athletes. Data collection in this study used three techniques, namely observation, interviews and documentation. The technique for determining informants in this study used a purposive sampling technique. The data analysis technique in this study is the interactive analysis model by Miles and Huberman. The stages of data analysis carried out in this development research as carried out are reducing data, presenting data data, and drawing conclusions. The results of this research are 1) The character value of Taqwa was realized by not leaving prayer services, not lying to the coach, and not taking friends' belonging, 2) the character value of Tanggap was applied by not intentionally hurting friends and helping friends who are in trouble whether asked or not, 3) the character value of Tangguh was realized by never giving up and being tenacious in achieving achievements, 4) The character value of Tanggon was applied by high discipline and dedication as well as controlling emotions to avoid fighting outside the ring, and 5) The character value of Trengginas was applied by being enthusiastic and working hard to achieve achievements.